2016
DOI: 10.1097/md.0000000000003488
|View full text |Cite|
|
Sign up to set email alerts
|

The DRD3 Ser9Gly Polymorphism Predicted Metabolic Change in Drug-Naive Patients With Bipolar II Disorder

Abstract: Patients with bipolar II disorder (BDII) have a higher prevalence rate of metabolic disturbance. Whether BDII itself, in addition to its current standard treatment, is a risk factor for metabolic syndrome warrants additional study. The dopamine receptor D3 (DRD3) gene, one of the candidate genes for BDII, is also involved in the dopaminergic system. We investigated whether it is related to changes in the metabolic indices of patients with BDII given 12 weeks of standard treatment.Patients with a first diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
6
0
2
Order By: Relevance
“…Interestingly, this variant has recently been also associated with low HDL levels in refractory schizophrenia (Pinto et al, 2018). Moreover, the most extensively DRD3 genetic variant (rs6280, also known as Ser9Gly) has been related to changes in TG and metabolic syndrome in treated patients with bipolar disorder (Chang et al, 2016). In our study, we found evidence for these two dopaminergic genes.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, this variant has recently been also associated with low HDL levels in refractory schizophrenia (Pinto et al, 2018). Moreover, the most extensively DRD3 genetic variant (rs6280, also known as Ser9Gly) has been related to changes in TG and metabolic syndrome in treated patients with bipolar disorder (Chang et al, 2016). In our study, we found evidence for these two dopaminergic genes.…”
Section: Discussionsupporting
confidence: 63%
“…[13] Presently, Ser9Gly polymorphisms are reported to be associated with acute pain in sickle cell disease, bipolar disorder, Parkinson's disease, and suicidical behaviors. [14][15][16][17] Recently, a number of molecular epidemiologic studies have addressed the association between Ser9Gly and schizophrenia risk. However, some reporters suggested that Ser9Gly was associated with the disease, [18,19] whereas the others found no association.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Presently, Ser9Gly polymorphisms are reported to be associated with acute pain in sickle cell disease, bipolar disorder, Parkinson's disease, and suicidical behaviors. [14][15][16][17] Recently, a number of molecular epidemiologic studies have addressed the association between Ser9Gly and schizophrenia risk. However, some reporters suggested that Ser9Gly was associated with the disease, [18,19] whereas the others found no association.…”
Section: Introductionmentioning
confidence: 99%